Pengaruh Green Accounting, Sustainability Report Disclosure, dan Green Investment terhadap Kinerja Keuangan - Ayuningtias, Puput Mia; Andayani, Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The operational activities of the basic materials sector in Indonesia have a significant environmental impact while affecting the company's financial performance. However, the implementation of sustainable practices as a strategy to mitigate environmental risks and improve financial performance is still limited and has not been implemented consistently. This study aims to analyze the influence of green accounting, sustainability reporting, and green investment on the company's financial performance. The population in this study includes basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period with a research sample of 20 companies selected based on certain criteria. The analysis method used was panel data regression with the help of Stata software version 17. The results of the empirical analysis show that green accounting and sustainability reporting do not have a significant influence on financial performance. Meanwhile, green investment has a negative and significant effect on financial performance. These findings indicate that while sustainability practices are gaining attention, not all green initiatives contribute positively to financial performance in the short term. Investor preferences are still focused on traditional financial indicators. In addition, the implementation of sustainability practices also requires considerable initial costs and is still considered voluntary implementation. These findings are expected to contribute to the development of the literature and assist stakeholders in optimizing sustainability practice strategies.